Kilka uwag o nieodnotowanych w słownikach współczesnej polszczyzny formacjach feminatywnych - Piotrowicz, Anna; Witaszek-Samborska, Małgorzata (Poznańskie Spotkania Językoznawcze, 2015)
Słowa, słowa... Czy je znasz? edited by Teresa Smółkowa (Kraków 2013), despite the fact that it has been recorded the male equivalents (eg. lack of forms jajcara, siecioholiczka, zasiłkowiczka, although there are jajcarz, siecioholik, zasiłkowicz). The authors proved the presence of such potential female names in the National Corpus of Polish and on the Internet using Google search. Of the 263 units unrecorded in the lexicon until 218 are present – with varying attendance – in the tested texts. This means that these female names are present in the social use. They do not limit themselves to the female equivalent of male names of professions. They also include semantic categories such as sports and hobbies, and names: representatives of certain attitudes and beliefs, women with specific characteristics of mental (including addicted women) and physical (including sick women), Internet users (including online offenders). These names are the result of suffixal derivation, mainly using the suffix -ka, eg. erasmuska < erasmus, netoholiczka < netoholik (but also such as: -ini/-yni, -ica/-yca, -anka and -ara), and the paradigmatic derivation, eg. dredziara < dredziarz, sprawna inaczej < sprawny inaczej. Functioning described in the article female names in the social circuit is proof that in the past ten years there has been a significant change in the Polish language in the pragmatic aspects of the nomination of women.